Vous êtes sur la page 1sur 9

# IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05

______________________________________________________________________________________

## Dual Equation of Indeﬁnite Problem with Three

Turning Points

R.Darzi, A. Dabbaghian, A. Neamaty and A. Jodayree Akbarfam

Abstract—We consider the diﬀerential equation to derive dual diﬀerential equations of the second order.
 2 2 In future paper we will apply the the dual equations to
−y + q(x)y = ρ φ (x)y f or x ∈ I := [0, 1], (i)
ﬁnd the solution of an inverse problem.
where I contain three turning points, that is here, ze-
ros of φ. Using of the asymptotic estimates provided 2 Notations
in [5] for a special fundamental system of solutions of
(i) in I, we study the inﬁnite product representation Let us consider the real second - order diﬀerential equa-
of solutions of (i). Also, we use the inﬁnite product tion
representations of the solutions to derive dual diﬀer-
ential equations of the second order. −y  + q(x)y = λφ2 (x)y , x ∈ I = [0, 1], (1)
Keywords: Turning point, Asymptotic form, where λ = ρ2 is a real parameter, φ2 and q are functions.
Hadamard factorization theorem, Inﬁnite products we suppose that
3

1 Introduction
φ2 (x) = (x − xν )lν φ0 (x)
Diﬀerential equations with turning points have various ν=1
applications in mathematics, elasticity, optics, geophysics
where 0 < x1 < x2 < x3 < 1, lν ∈ N , φ0 (x) > 0 for
and other branches of natural sciences(see[6,10,11]). The
x ∈ I, and φ0 is twice continuously diﬀerentiable on I.
importance of asymptotic analysis in obtaining informa-
In the other words, φ2 has in I, three zeros xν , of order
tion on the solution of a Sturm-Liouville equation with
lν , ν = 1, 2, 3, where l1 is even, l2 is odd and l3 is even.
multiple turning points was realized by Leung [11], Olver
In the terminology of [ 5 ], x1 is of type I, x2 is of type
[15-16], Heading [6], and Eberhard, Freiling and schnei-
IV and x3 is of type II. Zeros xν of φ2 are called turning
der in [4]. The results of [10,2,3] bring important inno-
points. We also assume that q is bounded and integrable
vations to the asymptotic approximation of solutions of
on I. Now let C(x, λ) be the solution of (1) corresponding
Sturm-Liouville equations with two turning points. Nea-
to the initial conditions C(0, λ) = 1, C  (0, λ) = 0. In
maty and Dabbaghian [13], authors obtained Asymptotic
order to represent the solution C(x, λ) as on Asymptotic
form of the solution of (i)with m turning points of odd-
form we use a suitable fundamental system of solutions
even order. Marasi and Jodayree [12], authors considered
(FSS) for Eq.(1) as constructed in [5 ]. Introducing some
that the weight function has m turning points that one
terminology at this point we write:
is of odd order and others are of even order. In [15], au-
thors considered duality for an indeﬁnite inverse Sturm-
Liouville problem with one turning point. In this paper 1
[1] ≡ 1 + O( ) , as λ −→ ∞,
we obtain The canonical product of the solution of diﬀer- λ
ential equation with turning points in a case where the
[α] ≡ α + O( ρσ10 ) where α ∈ C and
weight function has three turning points that x1 is of even
order, x2 is of odd order and x3 is of even order. Such, we
σ0 = min{μ1 , μ2 , μ3 },
use the inﬁnite product representations of the solutions
∗ R.Darzi,
Islamic Azad University Neka Branch , Neka, Iran (tel:
1
μν = ,
151-326-5358; fax: 152-578-2444; e-mail: r.darzi@umz.ac.ir). 2 + lν
A. Dabbaghian Islamic Azad University Neka Branch, Neka, Iran
(e-mail: a.dabbaghian@umz.ac.ir).
Dν, = [xν + , xν+1 − ] and Iν, = [xν−1 + , xν − ] ∪
A. Neamaty, Department of Mathematics, University of Mazan-
daran, Babolsar, Iran (e-mail: Neamaty@math.com). [xν − , xν + ] ∪ [xν + , xν+1 − ].
A. Jodayree Akbarfam, Department of Mathematics, University of
Tabriz, Tabriz, Iran (e-mail: Akbarfam@yahoo.com).

## (Advance online publication: 13 May 2010)

IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05
______________________________________________________________________________________

We know from [5] that in the sector and {U1,3 (x3 , ρ), U2,3 (x3 , ρ)}. From [5] we have
π √
S−1 = {ρ| arg ρ ∈ [− , 0]}, 2π 1 1 μ1
4 W1,1 (x1 , ρ) = (iρ) 2 −μ1 cscπμ1 eiπ(− 4 + 2 )
2
there exists an FSS of (1) {W1,1 (x, ρ), W2,1 (x, ρ)} 2μ1 ψ(x1 )
[1],
and such that Γ(1 − μ1 )
⎧ x

⎪ |φ(x)|− 12 ρ x1 |φ(t)|dt
[1], 0 ≤ x < x1 ,

⎨ e √
2π 1 1 μ1 2μ1 ψ(x1 )
W1,1 (x, ρ) = − 12 W2,1 (x1 , ρ) = (iρ) 2 −μ1 eiπ(− 4 + 2 ) [1],
⎪ |φ(x)|
⎪ x csc πμ1 2 Γ(1 − μ1 )

⎩ ρ x1 |φ(t)|dt
e [1], x1 < x < x2 ,
where

⎧ x − 12
x
1

⎪ − 12 −ρ x1 |φ(t)|dt ψ(x1 ) = lim φ (x){ φ(t)dt} 2 −μ1 . (3)
⎨ |φ(x)| e [1], 0 ≤ x < x1 , x→x1 x1
− 12
W2,1 (x, ρ) = |φ(x)|
 x sin πμ1 (2)

⎪ At the x = x2 , we have
⎩ −ρ x1 |φ(t)|dt
e [1], x1 < x < x2 . √
2π 1 2μ2 ψ(x2 )
Since x2 is of type IV, we also have the following FSS V1,2 (x2 , ρ) = (ρ) 2 −μ2 cscπμ2 [1],
2 Γ(1 − μ2 )
⎧ x

⎪ − 12 ρ x2 |φ(t)|dt
⎪ |φ(x)| e
⎪ [1], x1 < x < x2 , √
⎨ x 2π 1 πμ2 πμ2 2μ2 ψ(x2 )
V1,2 (x, ρ) = 1 − 12 πμ2 iρ |φ(t)|dt−i π V2,2 (x2 , ρ) = (ρ) 2 −μ2 e−i 2 sec( ) [1].

⎪ 2 |φ(x)|
 csc 2 {e x2 4
[1]+ 2 2 Γ(1 − μ2 )

⎪ −iρ x
⎩ e x2
π
|φ(t)|dt+i 4
[1]}, x2 < x < x3 , At the x = x3 , we have

⎧ x 2π 1 1 μ3 2μ3 ψ(x3 )

⎪ − 12 −ρ x2 |φ(t)|dt U1,3 (x3 , ρ) = (ρ) 2 −μ3 cscπμ3 eiπ( 4 − 2 ) [1],
⎨ |φ(x)| e [1], x1 < x < x2 , 2 Γ(1 − μ3 )
V2,2 (x, ρ) = − 12 πμ2
2|φ(x)|
x sin (3)

2
⎩ −iρ x2 |φ(t)|dt−i π4 √
e [1], x2 < x < x3 , 2π 1 1 μ3 2μ3 ψ(x3 )
U2,3 (x3 , ρ) = (ρ) 2 −μ3 eiπ( 4 − 2 ) [1].
2 Γ(1 − μ3 )
Since x3 , is of type II, we also have the following FSS
⎧ x

⎪ − 12 iρ x3 |φ(t)|dt 3 Asymptotic form of the solution

⎪ |φ(x)| e [1], x2 < x < x3 ,
⎨ x
U1,3 (x, ρ) = 1 iρ |φ(t)|dt We consider the diﬀerential equation (1) with the follow-

⎪ |φ(x)|− 2 cscπμ3 {e x3 [1] + i

⎪ x ing conditions
⎩ cos πμ e−iρ x3 |φ(t)|dt [1]}, x < x < 1,
3 3
C(0, λ) = 1 , C  (0, λ) = 0· (6)
⎧ x

⎪ |φ(x)|− 12
{e
−iρ |φ(t)|dt Applying the FSS {W1,1 (x, ρ), W2,1 (x, ρ)} for x ∈ I1, , we

⎪ x
x3
[1] + i

⎨ iρ |φ(t)|dt have
U2,3 (x, ρ) = cos πμ3 e x3 [1]}, x2 < x < x3 ,

⎪ |φ(x)|− 12
sin πμ (4) C(x, ρ) = c1 W1,1 (x, ρ) + c2 W2,1 (x, ρ), (7)

⎪ x 3

⎩ iρ x3 |φ(t)|dt
e [1], x3 < x < 1, that using of Cramer’s rule leads to the equation
It follows that the Wronskian of FSS satisﬁes 1
C(x, ρ) = (W  (0, ρ)W1,1 (x, ρ)
W (ρ) 2,1
W (ρ) ≡ W (W1,1 (x, ρ), W2,1 (x, ρ)) = −2ρ[1],
W (V1,2 (x, ρ), V2,2 (x, ρ)) = −2ρ[1],

W (U1,2 (x, ρ), U2,2 (x, ρ)) = −2iρ[1] −W1,1 (0, ρ)W2,1 (x, ρ)), (8)

## as ρ → ∞. where W (ρ) = −2ρ[1].

We also need Taking (2) in to account we derive
{W1,1 (x1 , ρ), W2,1 (x1 , ρ)}, {V1,2 (x2 , ρ), V2,2 (x2 , ρ)}

## (Advance online publication: 13 May 2010)

IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05
______________________________________________________________________________________

## Substituting (12) and estimates of V1,2 (x, ρ) and

⎧ x V2,2 (x, ρ) from (3) in the case
⎪ 1 − 12 1 ρ |φ(t)|dt
⎪ 2 |φ(x)|
 x |φ(0)| (e 0 [1]
2

⎪ x2 < x < x3 we derive the continuation of the solution

⎪ −ρ |φ(t)|dt

⎪ +e 0 [1]), 0 ≤ x < x1, to interval (x2 , x3 ) in the form:

1 − 12 1 x
2 |φ(x)| |φ(0)| 2 (csc πμ1 (ρ)
C(x, ρ) = (9) 1

⎪ x 1 1 iρ
C(x, ρ) = |φ(x)|− 2 |φ(0)| 2 (T1 (ρ)e x2
|φ(t)|dt
[1]+

⎪ ρ |φ(t)|dt

⎪ e x1 [1] + sin πμ1 (ρ) 2

⎪ x
⎩ −ρ x |φ(t)|dt
e 1 [1]), x1 < x < x2 . x
−iρ |φ(t)|dt
By virtue of (12), the following estimates are also valid: T2 (ρ)e x2
[1]) (15)
⎧ x
⎪ 1 − 12 1 ρ |φ(t)|dt where

⎪ 2 |φ(x)| |φ(0)| 2e 0

⎪  x2
⎨ Ek (x, ρ), 0 ≤ x < x1 1 πμ2 ρ |φ(t)|dt−i π
4
T1 (ρ) = csc πμ1 csc e 0 ,
C(x, ρ) = x (10) 2 2

⎪ |φ(x)| 2 |φ(0)| 2 csc πμ1 e 0
⎪ 1 − 1 1 ρ |φ(t)|dt
 x2

⎩ 2 1 πμ2 ρ
Ek (x, ρ), x1 < x < x2 , |φ(t)|dt+i π
4
T2 (ρ) = csc πμ1 csc e 0
2 2
where
 x2

ν(x) πμ2 −ρ |φ(t)|dt−i π
4
ραk βkn (x) +2 sin πμ1 sin e 0 ,
Ek (x, ρ) = [1] + e [bkn (x)], 2
n=1
or
and α−2 = α1 = −1 , α0 = −α−1 = i , βkν (x) = 0 1 1
, 0 < δ ≤ βk1 (x) < βk2 (x) < · · · ≤ βkν(x) (x) ≤ C(x, ρ) = 14 |φ(x)|− 2 |φ(0)| 2 csc πμ1 csc πμ2 2
2 max{R+ (1), R− (1)}, where the integer-valued functions  x2 x (16)
ν and bkn are constant in every interval Dj, , j = 1, 2, 3 ρ |φ(t)|dt+iρ |φ(t)|dt−i π
×e 0 x2 4
Ek (x, ρ), x2 < x < x3 ·
and
 x

## In addition, the value of C(x, ρ) at x = x2 can be calcu-

R+ (x) = max{0, φ2 (t)}dt , lated by taking account of (7) and (16)
0

 x

1 1
2π|φ(0)| 2 ρ 2 −μ2 2μ2 ψ(x2 )cscπμ1 cscπμ2
R− (x) = max{0, −φ2 (t)}dt· (11) C(x2 , ρ) =
4Γ(1 − μ2 )
0

## Similarly using of (5) and (11) for x = x1 we ﬁnd that  x2

√ 1 1 1 μ1 ×e
ρ
0
|φ(t)|dt
Ek (x2 , ρ). (17)
C(x1 , ρ) = 2π|φ(0)| 2 (iρ) 2 −μ1 cscπμ1 eiπ(− 4 + 2 )
 x1 Now for ﬁxed x ∈ (x2 , x3 ) and use (4) we determine the
2μ1 ψ(x1 ) ρ |φ(t)|dt connection coeﬃcients B1 (ρ), B2 (ρ) with
×e 0 Ek (x1 , ρ). (12)
4Γ(1 − μ1 )
C(x, ρ) = B1 (ρ)U1,3 (x, ρ)+B2 (ρ)U2,3 (x, ρ) , x2 < x < x3 ,
Hence we have estimated the solution of (1) deﬁned by the
initial conditions (9) in I1, . In order to ﬁnd the solution consequently
in I2 , we ﬁx x ∈ (x1 , x2 ) and use (3) and Cramer’s rule to x
3
determine the connection coeﬃcients N1 (ρ), N2 (ρ) with 1 1 iρ |φ(t)|dt
B1 (ρ) = |φ(0)| 2 T (ρ)e
1
x2
 x3 [1]−
2
C(x, ρ) = N1 (ρ)V1,2 (x, ρ) + N2 (ρ)V2,2 (x, ρ), 1 −iρ |φ(t)|dt
2 |φ(0)|
i
(13)
2 cos πμ3 T2 (ρ)e x2
[1], (18)
C  (x, ρ) = N1 (ρ)V1,2
 
(x, ρ) + N2 (ρ)V2,2 (x, ρ).  x3
1 −iρ |φ(t)|dt
Consequently B2 (ρ) = 2i |φ(0)| 2 T2 (ρ)e x2
[1]·
 x2
1 1 ρ |φ(t)|dt By the continuation of the solution to the interval (x3 , 1)
N1 (ρ) = |φ(0)| 2 csc πμ1 e 0 [1],
2

 x2 we have
1 1 −ρ |φ(t)|dt
N2 (ρ) = |φ(0)| 2 sin πμ1 e 0 [1]· (14)
2
C(x, ρ) = B1 (ρ)U1,3 (x, ρ) + B2 (ρ)U2,3 (x, ρ) (19)

## (Advance online publication: 13 May 2010)

IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05
______________________________________________________________________________________

## , x3 < x < 1, Such,for b ∈ (x1 , x2 ) has a countable set of negative eigen-

values {λ−n (b)}n≥0 :
then by (4) we obtain
x nπ 1
− 12 iρ |φ(t)|dt λ−
n (b) = i  b + O( ), (25)
C(x, ρ) = |φ(x)| [D1 (ρ)e x3
[1]+ |φ(t)|dt n
0

## x and for x = x2 similarly from (20) we have

−iρ |φ(t)|dt
D2 (ρ)e x3
[1]] , x3 < x < 1, (20)
nπ + ( πμ2 2 − π4 ) 1
−λ−
n (x2 ) =  x2 + O( ). (26)
where 0
|φ(t)|dt n
D1 (ρ) = B1 (ρ) csc πμ3 ,
For xυ < x < xυ+1 ,υ ≥ 2, the boundary value prob-
lem L1 , has an inﬁnite number of positive and negative
D2 (ρ) = iB1 (ρ) cos πμ3 + B2 (ρ) sin πμ3 · eigenvalues,

nπ − π4 1
By substituting (21) in (23)we obtain the leading term of λ+
n (b) =  b + O( ), (27)
|φ(t)|dt n
C(x, ρ) in (x3 , 1) as follows: x2

1 1
C(x, ρ) = 14 |φ(x)|− 2 |φ(0)| 2 csc πμ1 csc πμ2 2 csc πμ3
nπ − π4 1
λ−
n (b) = i  x2 + O( ). (28)
 x2 x (21) |φ(t)|dt n
ρ |φ(t)|dt+iρ |φ(t)|dt−i π 0
4
e 0 x2
Ek (x, ρ) , x3 < x < 1·
Similarly for x = x3 ,
In addition from (8) and (22) we can get the value of
nπ + ( πμ2 3 − π2 ) 1
C(x, ρ) at x = x3 : λ+
n (x3 ) =  x3 + O( ), (29)
|φ(t)|dt n
√ 1 1 1 μ3
x2
2π|φ(0)| 2 ρ 2 −μ3 2μ3 ψ(x3 )eiπ( 4 − 2 )
C(x3 , ρ) = (22)
8Γ(1 − μ3 ) nπ − π4 1
λ−
n (x3 ) =  x3 + O( ). (30)
x2
|φ(t)|dt n
πμ2
cscπμ1 csc cscπμ3 Since the solution C(x, ρ) of the Sturm -Liouville equa-
2
tion deﬁned by a ﬁxed set of initial conditions is an entire
 x2  x3 function of ρ for each ﬁxed x ∈ [0, 1], thus it follows from
ρ |φ(t)|dt+iρ |φ(t)|dt
×e 0 x2
Ek (x3 , ρ) the classical Hadamard’s factorization theorem that such
solution is expressible as an inﬁnite product.
Therefore, by using Hadamard’s theorem, C(x, λ) can be
represented in the form


4 The Asymptotic representation of the λ
C(x, λ) = c(b) (1 − ) (31)
canonical product n=1
λn (b)

We consider the boundary value problem L1 = where c(b) is a function independent of λ but may
L1 (φ2 (x), q(x), b) for Eq.(1) with boundary conditions depend on b. The sequence of λn is a zero set of C(b, λ)
for each b, so that C(b, λn ) = 0, which corresponds to
y(0, λ) = 1, y  (0, λ) = 0, y(b, λ) = 0.
eigenvalues of the boundary value problem L1
The boundary value problem L1 for b ∈ (0, x1 ) has a
countable set of negative eigenvalues {λ−
n (b)}n≥0 . The
asymptotic distribution of each function λn (b) is of the on the closed interval [0, b], 0 < b < x1 . We rewrite the
form inﬁnite product as

nπ 1
λ−
n (b) = i  b + O( ) (23)  λ  λ − λn (b)
|φ(t)|dt n C(b, λ) = c(b) (1 − ) = c1 (b) (32)
0 λn (b) zn2
and for x = x1 similarly from (15) we have with
 −z 2
nπ + ( πμ2 1 − π4 ) 1
−λ−
n (x1 ) =  x1 + O( ). (24) c1 (b) := c(b) n
,
0
|φ(t)|dt n λn (b)

## (Advance online publication: 13 May 2010)

IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05
______________________________________________________________________________________

nπ n −z 2  (λ − λn (x1 ))R−
2
(x1 )
where zn = R− (x) . Now (26) implies that λn (b) = × (37)
2
jn
1 + O( n12 ). It follows from [7] that the inﬁnite product n≥1
−zn2
λn (b) is absolutely convergent on any compact subin- where the sequence λn (x1 ) represents the sequence of neg-
2
−zn
terval of (0, x1 ). The function λn (b)
is continuous and so ative eigenvalues of the boundary value problem L1 on
the O-term is uniformly bounded in b. [0, x1 ].
Theorem 1. Let C(x, λ) be the solution of (1) satisfying proof. According to [14] the inﬁnite product
the initial conditions C(0, λ) = 1, C  (0, λ) = 0. Then for  (λ − λn (x1 ))R−
2
(x1 ) √
0 < x < x1 , 2
= 2μ1 Γ(1 + μ1 )[i λR− (x1 )]−μ1
jn
n≥1
 λ − λn (x)
C(x, λ) = |φ(x)| − 12 1
|φ(0)| R− (x)
2 (33) √ log n
zn2 Jμ1 (i λR− (x1 ))(1 + O( ))
n≥1 n
n2 π 2
where zn = R− nπ
(x) .
uniformly on the Circles |λ| = 2 (x ) .
R− 1

proof. Let {λn (x)} be the eigenvalues of the boundary Thus it follows from (15), we obtain
value problem L1 on [0, x], for ﬁxed x, 0 < x < x1 then 1 1
according to [9] we have |φ(0)| 2 ψ(x1 )R− (x1 ) 2 +μ1
A1 = .
√ 2μ1
 λ − λn (x) sinh R− (x) λ log n
( 2
)= √ (1 + O( )). (34) Theorem 3. For x1 < x < x2 ,
zn R− (x) λ n
1 1
C(x, λ) = |φ(x)|− 2 |φ(0)| 2 R− (x) csc πμ1
Thus from (13) and (35), we obtain
1 1  λ − λm (x)
c1 (x) = |φ(x)|− 2 |φ(0)| 2 R− (x). 2
(38)
zm
m≥1
Similarly for b = x1 again by Hadamard’s theorem we
that proof. Similarly for x1 < x < x2 , we use from (13) and
(35).
 λ
C(x1 , λ) = A (1 − ) (35) Theorem 4. For x = x2 , we have
λn (x1 ) 1 1
|φ(0)| 2 ψ(x2 )R− (x2 ) 2 +μ2 csc πμ1
where A is constant. Let jn , n = 1, 2, ... be the sequence C(x2 , λ) =
2μ2
of positive zeros of the Bessel function of order μ1 , then

## −jn2 1  (λ − λn (x2 ))R−

2
(x2 )
. (39)
2 (x )λ (x ) = 1 + O( n2 ),
R− 2
jn
1 n 1 n≥1

so the inﬁnite product proof. The proof is similar in every respect to that of
theorem 2 and so is omitted.
 −jn2 For x2 < x < x3 , the boundary value problem L1 on [0, x]
2
R− (x1 )λn (x1 ) has an inﬁnite number of positive and negative eigenval-
ues , say, respectively, {λ+ −
n }, {λn }. By Hadamard’s the-
are absolutely convergent.Consequently we may write as oram, the solution on [0, x], x2 < x < x3 is of the form
before,
 λ λ
C(x, λ) = d(x) (1 − )(1 − ). (40)
 (λ − λn (x1 ))R−
2 λ−
n (x) λ+
n (x)
(x)
C(x1 , λ) = A1 (36)
jn2 Now let j̃n , n = 1, 2, 3, ..., be the positive zeros of J1 (z),
derivative of the Bessel function of order one. The distri-
where bution of j̃n is of the form
 −jn2
A1 = A . mπ 2
2
R− (x1 )λn (x1 ) j̃n = m2 π 2 − + O(1), (41)
2
Theorem 2. For b = x1 , (see [1]). Consequently, we have
1
|φ(0)| 2 ψ(x1 )R− (x1 ) 2 +μ1
1
j̃n2 1
C(x1 , λ) = 2 + = 1 + O( 2 ),
2μ1 R+ (x)λn (x) n

## (Advance online publication: 13 May 2010)

IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05
______________________________________________________________________________________

−j̃n2 1  (λ − λ− 2
n (x))R− (x2 )
 (λ+ 2
n (x) − λ)R+ (x)
= 1 + O( 2 ). (42) × .
2 −
R− (x)λn (x) n 
jn2 
jn2
n≥1 n≥1

Consequently, the inﬁnite products proof. This follows from (24) and (47).
We can proceed similarly for b = x3 to obtain
 j̃n2  −j̃n2
2 (x)λ+ (x)
, 2 (x)λ− (x)
(43)  (λ − λ− 2
n (x3 ))R− (x2 )
R+ n R− n C(x3 , λ) = C3 (x)

jn
n≥1
are absolutely convergent for each x2 < x < x3 . There-
fore we may write
 (λ+ 2
n (x3 ) − λ)R+ (x3 )
 (λ − λ− 2 . (47)
n (x))R− (x2 ) rn
C(x, λ) = c2 (x) n≥1
j̃n2
where C3 (x) are constant and  jn is the sequence of pos-
 (λ+ 2 itive zeros J1 (z) and rn is the sequence of positive zeros
n (x) − λ)R+ (x) of Jμ3 + 32 (z).
(44)
j̃n2 Theorem 7. For x = x3 , we have
where √ 1 1 μ3
π|φ(0)| 2 ψ(x3 )R− (x2 ) 2 R+ (x3 )
C(x3 , λ) = 1 (48)
 j̃n2  −j̃n2 4Γ(μ3 + 2 )
c2 (x) = d(x) .
R+ (x)λ+
2
n (x) R− (x)λ−
2
n (x) × csc πμ1 csc π μ22

## Theorem 5. For x2 < x < x3 ,  (λ − λ− 2  (λ+ 2

n (x3 ))R− (x2 ) n (x3 ) − λ)R+ (x3 )
× .

jn rn
π 1 1
n≥1 n≥1
C(x, λ) = |φ(x)|− 2 |φ(0)| 2
8
proof. We have
1 μ2  (λ − λ− 2
n (x3 ))R− (x2 )
 (λ+ 2
n (x3 ) − λ)R+ (x3 )
×(R− (x)R+ (x)) 2 csc πμ1 csc π
2 
jn rn
n≥1 n≥1

 (λ − λ− 2
n (x))R− (x2 )
 (λ+ 2
n (x) − λ)R+ (x) 1 √
× . (45) 1 1
= 2μ3 + 2 Γ(μ3 + )(R+ (x3 ) λ)−(μ3 − 2 ) M, (49)

jn2 
jn2 2
n≥1 n≥1
where
proof. From [14] we have
1 πμ3
M=
eρR− (x2 )+iρR+ (x3 )− 2 i [1],
 (λ − λ− 2
n (x))R− (x2 )
 (λ+ 2
n (x) − λ)R+ (x) 2πρ R+ (x3 )R− (x2 )

jn2 
jn2
n≥1 n≥1 thus, we get

4e R− (x) λ √ π 1 √ 1 1μ3
= √ {cos(R+ (x) λ − 4 ) + O( √ )} π|φ(0)| 2 ψ(x3 )R− (x2 ) 2 R+ (x3 )
1
2
1
2 λ C3 (x) = 1
πR− (x)R+ (x) λ 4Γ(μ3 + 2 )
as λ → ∞. Thus we get μ2
csc πμ1 csc π .
π 1 1 1 2
C2 (x) = |φ(x)|− 2 |φ(0)| 2 (R− (x)R+ (x)) 2
8
μ2 5 The dual equation
csc πμ1 csc π .
2
In this section, we drive the dual equations associated
Theorem 6. For x3 < x < 1,
with (1) by use of inﬁnite product representation.
π 1 1 1 Theorem 8. For 0 < x < x1 , the sequences of functions
C(x, λ) = |φ(x)|− 2 |φ(0)| 2 (R− (x)R+ (x)) 2
8 {λn (x)} satisfy
2c (x)λn λ λn (x) −1
μ2 λ + + 2λn λn 2 (1 − )
csc πμ1 csc π csc πμ3 (46) c(x) λi λi (x)
2 i=n,1≤i

## (Advance online publication: 13 May 2010)

IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05
______________________________________________________________________________________

## (λn )2 λi λn (x) −1

−2 = 0, (50) −c(x)Tn (1 − ) −
λn λ2i λi (x)
i=n,1≤i

## where c(x) is deﬁned in (35).

proof. For 0 < x < x1 ,the condition C(x, λn (x)) = 0
cλn Tn 1 λn (x) −1
gives, (1 − ) .
λn λi λi (x)
i=n,1≤i
∂C ∂C 
+ λ = 0,
∂x ∂λ n Placing these terms into (55), we obtain
The sequence λn represents the sequence of negative 2c (x)λn
λ + +
eigenvalues of L1 on (0, x1 ). With diﬀerentiating again c(x)
∂2C ∂2C  ∂ 2 C  2 ∂C 
+2 λn + (λ ) + λ = 0. (51) λ λn (x) −1 (λ )2
∂x2 ∂x∂λ ∂λ2 n ∂λ n 2λn λn (1 − ) − 2 n = 0. (55)
2
λi λi (x) λn
i=n,1≤i
The ﬁrst term in (53) is zero at (x,n (x)) by virtue of (1).
Thus where c(x) is deﬁned in (35).
2
∂ C  2
∂ C  2 ∂C  We note that dividing Eq. (53) by λn and integrating
2 λ + (λ ) +
∂x∂λ n ∂λ2 n
λ = 0.
∂λ n
(52) from a ﬁxed number α = −1 up to x, we obtain

## Now, we ﬁrst calculate the various derivatives of C(x, λ).

λ2n (x)λn (α)c2 (α) −2sn (x,λn )
In the case, from (35), it can be written λn (x) = e , (56)
λ2n (α)c2 (x)

 λ where
C(x, λ) = c(x) (1 − ). (53)

λk (x)
k=1 x
λi λn
Sn (x, λn ) = (λi − λn )−1 .
2 2 λi
We calculate ∂C ∂ C ∂ C
∂λ , ∂λ2 and ∂x∂λ at the points (x, λn (x))
i=n α

∂2C
by using (56). In forming ∂λ∂x from (56), the interchange Similarly, for x1 < x < x2 , using λn , the sequence of
of summation and diﬀerentiation in negative eigenvalues on (x1 , x2 ) and
d λ ∞
(1 − )  λ
dx
k≥1
λk (x) C(x, λ) = u(x) (1 − ), (57)
λk (x)
k=1
will be valid if the diﬀerentiated series 1 1
where u(x) = |φ(x)|− 2 |φ(0)| 2 R− (x) csc πμ1 , we obtain
−λn (x)λk (x)
(λk (x) − λn (x))λk (x) λ2n (x)λn (α)u2 (α) −2sn (x,λn )
k=n λn (x) = e , (58)
λ2n (α)u2 (x)
is uniformly convergent which is the case from [16]. We
deﬁne Tn by  x
λi λn
Sn (x, λn ) = (λi − λn )−1 .
 β λi
λn (x) i=n
Tn = Tn (x, λn (x)) = (1 − ). (54)
λk (x) where x1 < β < x < x2 .
k=n,1≤k

We have ∂2C  ∂ 2 C  2 ∂C 
2 λn + (λ ) + λ = 0. (59)
∂x∂λ ∂λ2 n ∂λ n
∂C −cTn
(x, λn ) = , Theorem 9. For x2 < x < x3 , the sequences of functions
∂λ λn (x)
{λ+ −
n } and {λn } satisfy

## ∂2C 2cTn 1 λn (x) −1  2d (x)λ+



(x, λn ) = (1 − ) , λ+
n +
n
∂λ2 λn (x) λi λi (x) d(x)
i=n,1≤i

λ+ + 
+ −1
∂2C −c Tn cλ Tn

i (λi (x) − λn (x))
+2λ+ +
n λn {
(x, λn ) = + 2n λi+
∂λ∂x λn (x) λn (x) i=n,1≤i

## (Advance online publication: 13 May 2010)

IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05
______________________________________________________________________________________

λ− (λ+ 2
d(x)λ+


n ) n Hn Gn 1
+ i
(λ+ +
i (x) − λn (x))
−1
}−2 = 0, (60) − +
λ − +
λn λn (x) λ (x) − λ+

1≤i i n (x)
i=n i

2d (x)λ−

λ−
(λ− + −1

λ− + n −d(x)Hn Gn i
i (x) − λn (x))
n
d(x) 1≤i
λ−
i

λ−



+2λ− +
(λ− − −1 λ+
n λn { i (x) − λn (x))
i + + −1
−d(x)Hn Gn i
+ (λi (x) − λn (x))
i=n,1≤i
λ−
i λ
1≤i,i=n i

## λ+ (λ− (x) − λ− (x))−1 (λ− )2


n
+ i i
} − 2 n− = 0, (61)
i=n
λ+
i λn

d(x)λ+


proof. The conditions ϕ(x, λ+ n H n Gn 1
n (x)) = 0 and −

ϕ(x, λn (x)) = 0 give the equations λ+
n (x) λ
1≤i,i=n i
+
(x) − λ+
n (x)

## ∂ 2 ϕ + ∂ 2 ϕ + 2 ∂ϕ + Placing these terms into (65), we obtain (63).

2 λ + (λ ) + λ = 0,
∂x∂λ n ∂λ2 n ∂λ n Similarly for negative Eigenvalue λ− n (x) we get (64). In

−
this case, dividing Eq. (63) by λ+
n , Eq. (64) by λ n and
∂ 2 ϕ − ∂ 2 ϕ − 2 ∂ϕ − integrating from b up to x, we obtain
2 λ + (λ ) + λ = 0. (62)
∂x∂λ n ∂λ2 n ∂λ n λ+2 + 2 

n (x)λn (b)d (b) 2Zn (x,λ+ −
λ+
n (x) = +2 e n ,λn ) , (66)
From (43), we have λn (b)d2 (x)
 λ λ
C(x, λ) = d(x) (1 − )(1 − + ). (63) λ−2 − 2 

λ− 
n (x)λn (b)d (b) 2Zn (x,λ− +
n (x) λ n (x) λ−
n (x) = −2 2
e n ,λn ) , (67)
λn (b)d (x)
As before, we calculate the various derivatives of C(x, λ)
and evaluate these at the ﬁxed points (x, λ+ where
n (x)),
(x, λ−
n (x)). Suppose  x
λ+

+
i λn +
Zn (x, λ− +
n , λn ) =
+ −1
+ (λi − λn ) dν
 λ+ λi
n (x) b
Gn = Gn (x, λ+
n (x)) = (1 − ), (64) i=n

k=n,1≤k
λ+
k (x)
 x
λ− +


i λn − + −1

+ − (λi − λn ) dν (68)
λ+
n (x) b λi
Hn = Hn (x, λ+
n (x)) = (1 − − ). (65) i

1≤k
λk (x)
Similarly, for x3 < x < 1,

We have  λ+2 (x)λ+ (1)f 2 (1) 2Zn (x,λ+ −
λ+
n (x) = n +2 n 2 e n ,λn ) , (69)
∂C −dHn Gn λn (1)f (x)
(x, λ+
n) = ,
∂λ λ+
n (x)

 λ−2 − 2
n (x)λn (1)f (1) 2Zn (x,λ− +
λ−
n (x) = e n ,λn ) , (70)
∂2C 2dHn Gn 1 2dHn Gn −2 2
λn (1)f (x)
(x, λ+
n) = + +
∂λ 2
λ+ − +
n (x) 1≤i λi (x) − λn (x) λn (x)
where
 1
λ+

+
i λn +
1 Zn (x, λ− +
n , λn ) = + −1
+ (λi − λn ) dν
+ , λi
λ+
x
λ
1≤i,i=n i
(x) − n (x)
i=n

 1
λ− +

 i λn − + −1
∂2C −d (x)Hn Gn d(x)λ+
n Hn Gn + − (λi − λn ) dν. (71)
(x, λ+
n) = + + +2 i x λi
∂λ∂x λn (x) λn (x)

## (Advance online publication: 13 May 2010)

IAENG International Journal of Applied Mathematics, 40:2, IJAM_40_2_05
______________________________________________________________________________________

## References [14] Ne, A. , “The canonical product of the solution of

the Sturm-Liouville problems,” Iran. J. Sci. Tech-
[1] He, J., “Global phase-integral methods, ” Quart. J. nol. Trans. A, V2.
Mech. Appl. Math, V30, pp. 281-302.
[15] Jo, A., Mingarelli, A. B. , “Duality for an indeﬁnite
[2] Ka, N.D.,“symptotic theory of second order diﬀeren- inverse Sturm-Liouville problem,” J. Math. Anal.
tial equations with two simple turning points,” Ra- Appl., V312, pp. 435-463.
tion. Mech. Anal, V2, pp. 129-150.
[16] Jo, A., Pourreza, E., “A research note on the second
[3] Le,A., “Distribution of eigenvalues in the presence of order diﬀerential equation,” Int. J. Appl., V1, pp.
higher order turning points, ” Trans. Amer. Math. 849-862.
Soc, V229, pp. 111-135.

## [4] Ol, F.WJ., “Connection formulas for second-order

diﬀerential equations having an arbitrary number of
turning points of arbitrary multiplicities,” SIAM J.
Math. Anal, V8, pp. 673-700.

## [5] Ol, F.W.J., “Connection formulas for second-order

diﬀerential equations with multiple turning points,”
SIAM J. Math. Anal, V8, pp. 127-154

## [6] Eb, W., Freiling, A., “On the distribution of the

eigenvalues of a class of indeﬁnite eigenvalue prob-
lem,” J.Diﬀerential Integral Equations , V3, N1, pp.
1167-1179.

## [7] Do, A.A., “Visual Servoing by Partitioning Degrees

of Freedom,” Amer. Math. Soc. Transl. Ser, V2,
N16, pp. 1-101.

## [8] Dy, A.X., “Asymptotics of the eigenvalues of an

indeﬁnite Sturm-Liouville problem,” Math. Notes,
V68, NI, pp. 120-124.

## [9] Eb, W., Freiling, G., Schneider, A., “Connection for-

mulae for second-order diﬀerential equations with a
complex parameter and having an arbitrary number
of turning points,” Math. Nachr, V165, pp. 205-229.

## [10] Ma, A., Jodayree Akbarfam, “On the canoni-

cal solution of indeﬁnits problem with m turn-
ing points of even order,” J. Math. anal. Appl.,
doi:10.1016/j.jmaa.2006.10.049.

## [11] Ne, A. , Dabbaghian, A., “Asymptotic form of the

solution of Sturm-Liouville problem with m turning
points of odd-even order,” Far. East. J. Appl. Math,
V29, N2, pp. 261-271.

## [12] Jo, A., Mingarelli, A. B., “The canonical product of

the solution of the Sturm-Liouville equation in one
turning point case,” Canad. Appl. Math. Quart, V8,
N4, pp. 305-320.

## [13] Ab, M., Stegun, J. A., “Handbook of Mathematical

Functions,” Appl. Math. Ser., U. S. Govt. Printing
Oﬃce, Washington,DC.